RELIGIOUS MODERATION IN PUBLIC SERVICE POLICY: BRIDGING BUREAUCRATIC NEUTRALITY AND SOCIAL HARMONY IN INDONESIA - Abdul Hafith; Abdul Malik; Winengan (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Religious moderation serves as a fundamental principle in the context of public service in Indonesia, where religious, cultural, and ethnic diversity demands fair, inclusive, and civilized governance. This study aims to analyze the role of religious moderation in public service policy in Indonesia, particularly in bridging the relationship between bureaucratic neutrality and social harmony within a multicultural society. To date, studies on religious moderation have largely focused on education and interfaith dialogue, while the dimensions of public policy and bureaucratic culture remain underexplored. Using a qualitative approach through policy analysis and literature review, this research examines how the values of religious moderation tawasuth (balance), tasamuh (tolerance), ‘adl (justice), and musawah (equality) can be integrated into an inclusive, fair, and ethical public service system. The findings indicate that the internalization of moderation values within public policy can strengthen governmental ethics, enhance public trust, and reinforce social cohesion amid diversity. This study also proposes a conceptual model called Moderation-Based Public Service Governance (MBPSG) as a new framework for public service management grounded in the values of religious moderation, balancing administrative efficiency with social justice.